Portuguese Colonial War veterans physical health: A systematic review - Maia,Ângela (2019)
After 45 years, little is known about Portuguese Colonial War veterans physical health. This systematic review aimed to fill this gap. Following PRISMA guidelines, searches were conducted, on November 2018, in seven electronic databases for the inclusion of Portuguese or English quantitative, qualitative, or mixed-method published studies, unpublished masters or doctoral theses and research reports that focused on physical health. Seventy-one studies were identified; 10 were considered eligible. Veterans reported several physical complaints and chronic diseases, as well as risk behaviors and health services use for the relief of psychological symptoms. Differences were found between veterans and nonveterans, and veterans with and without posttraumatic stress disorder (PTSD). Combat exposure and PTSD were associated with physical morbidity, in which PTSD was a full mediator. Implications for practice and recommendation for future research are discussed.